2020
DOI: 10.1101/2020.08.11.246777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomically Complex Human Angiosarcoma and Canine Hemangiosarcoma Establish Convergent Angiogenic Transcriptional Programs Driven by Novel Gene Fusions

Abstract: Sporadic angiosarcomas (ASs) are aggressive vascular sarcomas whose rarity and genomic complexity present significant obstacles in deciphering the pathogenic significance of individual genetic alterations. Numerous fusion genes have been identified across multiple types of cancers, but their existence and significance remain unclear in sporadic ASs. In this study, we leveraged RNA sequencing data from thirteen human ASs and 76 spontaneous canine hemangiosarcomas (HSAs) to identify fusion genes associated with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…We and others showed previously that canine hemangiosarcoma cells could form hemangiosarcomas in NSG mice. 7,21,24,35,36 We also observed that some of the NSG mice inoculated with SB-HSA cells or with another cell line called Emma-brain (EFB), and some BNX mice inoculated with DHSA-1426 canine patient-derived tumor fragments developed what appeared to be round cell tumors. Four mice that received 5 × 10 6 SB-HSA cells intraperitoneally and one of four mice that received 2 × 10 6 EFB cells subcutaneously died acutely two weeks after inoculation.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…We and others showed previously that canine hemangiosarcoma cells could form hemangiosarcomas in NSG mice. 7,21,24,35,36 We also observed that some of the NSG mice inoculated with SB-HSA cells or with another cell line called Emma-brain (EFB), and some BNX mice inoculated with DHSA-1426 canine patient-derived tumor fragments developed what appeared to be round cell tumors. Four mice that received 5 × 10 6 SB-HSA cells intraperitoneally and one of four mice that received 2 × 10 6 EFB cells subcutaneously died acutely two weeks after inoculation.…”
Section: Resultsmentioning
confidence: 76%
“…Canine hemangiosarcomas can be classified into angiogenic, inflammatory, and adipogenic subtypes based on their transcriptional programs ( Figure S1A ). 4,7 This separation is prognostically significant: of the 43 dogs in this cohort for which we had treatment and outcome data, those with inflammatory hemangiosarcomas accounted for nearly all that showed prolonged survival (>150 days, Figure S1B ). Intriguingly, the subset of dogs whose hemangiosarcomas had a predominant angiogenic phenotype could be further subdivided into a group with a “pure angiogenic” molecular signature and a group with a “mixed angiogenic and inflammatory” molecular signature.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations